2009
DOI: 10.2151/sola.2009-046
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Kinetic Energy Spectrum of NICAM Model Atmosphere

Abstract: In this study, characteristics of the energy spectrum in the zonal wavenumber domain are examined for the cloud resolving global model NICAM. A series of numerical experiments are conducted for NICAM with various horizontal resolutions from 224 km (glevel-5) to 7.0 km (glevel-10) using the T2K-Tsukuba System and 3.5 km (glevel-11) using the Earth Simulator (ES). The energy spectra of most of horizontal resolutions obey k 3 power law in synoptic and sub-synoptic scales (wavenumbers k = 5 to 30). However, the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 13 publications
3
18
0
Order By: Relevance
“…The result of this study may indicate that the shifting wavenumber from k −3 to k −5/3 is determined just as a crossing wavenumber of Rossby wave and gravity wave spectra. Terasaki et al (2009) found that the energy spectrum of the vertical motion becomes white noise using NICAM experiment (3.5 km horizontal grid spacing), which has almost the same energy level at any horizontal scales. It is suggested that the k −5/3 power spectral law in stratified turbulence may be explained by the saturation theory of the vertical motion.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The result of this study may indicate that the shifting wavenumber from k −3 to k −5/3 is determined just as a crossing wavenumber of Rossby wave and gravity wave spectra. Terasaki et al (2009) found that the energy spectrum of the vertical motion becomes white noise using NICAM experiment (3.5 km horizontal grid spacing), which has almost the same energy level at any horizontal scales. It is suggested that the k −5/3 power spectral law in stratified turbulence may be explained by the saturation theory of the vertical motion.…”
Section: Resultsmentioning
confidence: 88%
“…According to their results, the nonlinear interactions between geostrophic and gravitational modes play a crucial role in the downscale energy cascades for forming the k −5/3 spectrum. Terasaki et al (2009) showed the kinetic energy spectra for zonal wind and vertical wind components simulated by NICAM (Non-hydrostatic ICosahedral Atmospheric Model) with horizontal grid spacing from 224 km to 3.5 km. They confirmed that the spectra of zonal wind components follows k −5/3 law in the mesoscale for 7.0 km and 3.5 km experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The convective structure near the tropopause was also analyzed by Kubokawa et al (2012). The energy spectrum and similar frequency spectra of the high-resolution data were analyzed by Terasaki et al (2009) and Tsuchiya et al (2011).…”
Section: Scientific Overview Of Nicammentioning
confidence: 99%
“…Likewise, Žagar et al (2009a, b) applied the 3D normal mode energetics to four different analyses and compared energy levels of gravity modes. With regard to model output, Terasaki et al (2009) investigated the details of the kinetic energy spectrum of Non-hydrostatic Icosahedral Atmospheric Model (NICAM) for different resolutions by using Fourier analysis, and they showed that the highest resolution model can exhibit the shift of the energy slopes from the -3 power to -5/3 power laws.…”
Section: Introductionmentioning
confidence: 99%